A tendência modelagem matemática na feira de matematica da Escola Nossa Senhora do Rosario – Marituba – PA - SANTANA, Jhonata da Costa (2019)
The Mathematics Fairs are fruits of university extension projects, which began at the Regional University of Blumenal, idealized by professors Vilmar José Zermiani and José Valdir Floriani. In the state of Pará, the 1st Mathematical Fair of the Nossa Senhora do Rosário School - Marituba - PA, was held as one of the actions of the extension project "Pedagogical Laboratory of Basic Education" of the Federal University of Pará. I noticed that in some works the signs of the tendency of Mathematical Modeling. The objective of this monograph is to analyze the works carried out in the First Mathematics Fair of the Nossa Senhora do Rosário School in the form "Applied Mathematics and / or its interrelationships with other disciplines", and verify if there are any indications of the use of the method of Mathematical Modeling in teaching. The methodology used was based on a qualitative approach (Chizotti, 2006), and exploratory research was used as a research technique (Gil, 2008), in which a bibliographic survey was made based on Biembengut and Hein (2007), Chaves (2005); and Zermiani (2003), a documentary analysis of the abstracts of papers presented at the Mathematics Fair of the Nossa Senhora do Rosário school, and a semi-structured interview with a teacher who observed the use of the trend. The results obtained were the use of Mathematical Modeling at the fair, because it allowed teachers to make use of new Teaching Methodologies, making references to the local environment of the students.